Tingkat Relevansi dan Implementasi Landasan Filosofis, Sosiologis, dan Yuridis terhadap Kualitas Pembentukan Peraturan Daerah di Indonesia - Zulrijal Bushido Gani; Najamuddin Gani (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
The formation of regional regulations (Perda) is a constitutional derivative of the implementation of regional autonomy within the framework of the Indonesian legal system. Substantively, Perda function as regulatory instruments aimed at accommodating the specific interests of local communities, in line with fundamental values, contextual needs, and the hierarchy of applicable laws and regulations. However, the high frequency of annulment or cancellation of Perda indicates dissonance or non-compliance with the principles of sound legislative formation. This phenomenon raises the urgency to review the extent to which philosophical, sociological, and legal foundations have been internalized and comprehensively implemented in the regional legislative process. Therefore, this study focuses on analyzing the relevance of these three fundamental foundations to the quality and legitimacy of regional legal products. This study adopts a normative-juridical legal research method, involving descriptive analysis of the corpus of laws and regulations, legal doctrine, and the empirical practice of Perda formation. The results highlight that: the philosophical foundation provides a normative orientation in the form of ethical-teleological values ​​and goals; the sociological foundation reflects the actual needs and social realities of the communities subject to regulation; Meanwhile, the legal basis guarantees formal legality and vertical and horizontal consistency with the national legal system. Key findings indicate that these three foundations are inherently relevant and complementary in determining the quality of regional regulations. Synergy and harmonious integration between them are essential prerequisites for producing regional legal products that have legal validity, are capable of upholding substantive justice, and are responsive to the dynamics of public needs.